SISTEM INFORMASI PENGARSIPAN PADA KANTOR KELURAHAN BALAM SEMPURNA KOTA - Ira Mirantika Br. Ginting; Jamaluddin Jamaluddin; Rimbun Siringoringo (Universitas Methodist Indonesia, 2021)
The Balam Sempurna Kota Kelurahan office needs an information system that can help with mail management. Management of letters in the City Perfect Balam Kelurahan Office that uses manual errors often occur in the storage of letter data and search letters. The filing information system in the Balam Sempurna Kota Kelurahan Office is very necessary, in addition to the management letter, it is also needed to make the letter faster and more efficient. This filing information system changes the way in which manual mail is stored into a computerized letter archive in the form of a computerized system. This filing information system provides good benefits for the organization. The archiving information system implementation displays a user interface, which is: the interface of all users and the administrator's interface. Filing information systems can make outgoing mail faster and more efficient, sending incoming mail data. Can be used to manage the mail archive, so that it can be managed properly.